Interface Tracking Simulation for Subcooled Flow Boiling Using VOSET Method - Ling, Kong; Zhang, Shuai; Liu, Wenxing; Sui, Xiaowei; Tao, Wenquan (Frontiers in Energy Research, 2021)
This article presents a numerical simulation on subcooled flow boiling at a high-pressure condition. An interface tracking method, VOSET, was used to handle the moving interface, and conjugate heat transfer between the wall and the fluid was included in the numerical model. In order to consider the evaporation on the microlayer below a growing bubble, a depletable micorlayer model was employed. Our simulation illustrated typical processes of subcooled boiling flow including bubble sliding, coalescence, detachment and annihilation, and revealed many mechanisms in increasing the heat transfer coefficient. A transition in flow regime from isolated bubbly flow to elongated bubbly flow was reproduced by our simulations. The void fraction obtained by time-averaging the volume fraction of the vapor phase under various flow conditions was analyzed.